Sustainability disclosure and the relationship with board characteristics and assurance - Nickolas Patrick Garcia Duarte; Rodrigo Vicente dos Prazeres; Umbelina Lagioia; Juliana Gonçalves de Araújo; Luiz Carlos Marques dos Anjos (Revista Contabilidade & Finanças)
Abstract This study aims to analyze the influence of internal factors within organizations, such as board characteristics and the practice of external assurance, on the quality of sustainability reports of Brazilian companies. As a gap, to examine the level of compliance of Brazilian companies' sustainability reports with the methodology suggested by IR. The objective is to assess the effects of the external assurance variable on the compliance of sustainability information. The relevance of this study is to assess entities' commitment to socio-environmental responsibility, transparency, and accountability to stakeholders, while fostering sustainable practices and enhancing corporate image nationally. This study provides a discussion on the current state of board compositions, highlighting the high number of directors and the low proportion of women, despite the significant positive influence women have on sustainability disclosure. The results related to the "External Assurance" variable may encourage more organizations to adopt this practice, with the expectation of demonstrating greater alignment with suggested methodologies. An adaptation of the method by Sun et al. (2022) was used, analyzing report quality across nine stakeholder-related topics. An unbalanced panel data analysis was conducted, using random effects estimated by GLS, on a sample of 357 reports from 49 Brazilian companies between 2014 and 2022. The variable "Presence of Women on Boards (PWOB)" was found to be significant in relation to the quality of sustainability disclosures, indicating that diversity contributes to greater prestige and attention to social issues. The variables "Board Committees (BC)" and "External Assurance (EA)" showed a positive relationship, supporting the board's ability to respond to different pressures and reinforcing transparent and reliable approaches in communication with stakeholders.